A writer's guide to education scholarship: Qualitative education scholarship (part 2). Issue 2 (19th May 2017) - Chan, Teresa M.; Ting, Daniel K.; Hall, Andrew Koch; Murnaghan, Aleisha; Thoma, Brent; McEwen, Jill; Yarris, Lalena M.
Abstract: Objective: Education scholarship can be conducted using a variety of methods, from quantitative experiments to qualitative studies. Qualitative methods are less commonly used in emergency medicine (EM) education research but are well-suited to explore complex educational problems and generate hypotheses. We aimed to review the literature to provide resources to guide educators who wish to conduct qualitative research in EM education. Methods: We conducted a scoping review to outline: 1) a list of journals that regularly publish qualitative educational papers; 2) an aggregate set of quality markers for qualitative educational research and scholarship; and 3) a list of quality checklists for qualitative educational research and scholarship. Results: We found nine journals that have published more than one qualitative educational research paper in EM. From the literature, we identified 39 quality markers that were grouped into 10 themes: Initial Grounding Work (preparation, background); Goals, Problem Statement, or Question; Methods (general considerations); Sampling Techniques; Data Collection Techniques; Data Interpretation and Theory Generation; Measures to Optimize Rigour and Trustworthiness; Relevance to the Field; Evidence of Reflective Practice; Dissemination and Reporting. Lastly, five quality checklists were found for guiding educators in reporting their qualitative work. Conclusion: Many problems that EM educators face are well-suited to exploration using qualitative methods. The results of our scoping review provide publication venues, quality indicators, and checklists that may be useful to EM educators embarking on qualitative projects. RÉSUMÉ: Introduction: Les travaux de recherche en enseignement peuvent être menés selon différentes méthodes, depuis les études expérimentales quantitatives jusqu'aux études qualitatives. Les méthodes qualitatives sont moins utilisées que les autres dans la recherche en enseignement de la médecine d'urgence (MU), mais elles conviennent très bien à l'étude de problèmes complexes en enseignement et à l'émission d'hypothèses. Aussi avons-nous procédé à un examen de la documentation afin de proposer des ressources aux éducateurs qui désirent réaliser de la recherche qualitative en enseignement de la MU. Méthode: Nous avons effectué un examen de la portée afin : 1) de dresser une liste de revues qui publient souvent des travaux de recherche qualitative en enseignement; 2) d'établir un ensemble de marqueurs de qualité s'appliquant à la recherche qualitative en enseignement et aux travaux scientifiques; 3) de relever des listes de vérification de la qualité s'appliquant à la recherche qualitative en enseignement et aux travaux scientifiques. Résultats: La recherche a permis de recenser neuf revues qui avaient publié plus d'un travail de recherche qualitative en enseignement de la MU. Il s'est dégagé de l'examen de la documentation 39 marqueurs de qualité, groupés en 10 thèmes : les travaux préliminaires (les préparatifs, le contexte); le but, l'énoncé du problème ou la question; la méthode (généralités); la technique d'échantillonnage; la technique de collecte de données; l'interprétation des données et l'élaboration de théories; les mesures d'amélioration de la rigueur et de la véracité; la pertinence de la recherche dans le domaine; les signes de la pratique réflexive; la diffusion et l'établissement de rapports. Enfin se sont dégagées de la recension cinq listes de vérification de la qualité susceptibles d'aider les éducateurs dans l'établissement de rapports sur leurs travaux de recherche qualitative. Discussion: De nombreux problèmes auxquels font face les éducateurs en MU se prêtent bien à la recherche menée à l'aide de méthodes qualitatives. L'examen de la portée a permis de relever différents éditeurs, des indicateurs de qualité et des listes de vérification susceptibles de guider les éducateurs en MU qui désirent faire de la recherche qualitative.